2003
DOI: 10.2355/isijinternational.43.950
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Arc-Electrodes Systems for High Temperature Materials Processing by Computational Simulation

Abstract: Thermofluid analysis of an arc flow and the evaluation of the cathode lifetime have been conducted by a computational simulation for the performance improvement of arc-electrodes systems. The effects of arc current, electrode gap, inlet gas flow rate and cathode vertex angle on the temperature and velocity fields of an arc flow are clarified by parametric computations to optimize the operating conditions and torch geometry. The temperature field by an arc flow model shows the quantitative agreement with the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Several studies [1][2][3][4][5] have been conducted by experimental observation and numerical simulation in order to investigate the electrode consumption. Sadek et al 1) observed the electrodes tip microstructure after a TIG welding operation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [1][2][3][4][5] have been conducted by experimental observation and numerical simulation in order to investigate the electrode consumption. Sadek et al 1) observed the electrodes tip microstructure after a TIG welding operation.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature measurement could not be performed in this report, however, it shows a reasonable temperature level written in the literature. 5) Figure 12 presents the calculated velocity field without and with DC magnetic field. The velocity at the nozzle outlet reaches to 160 m/s, however, it becomes the value of 120 m/s at the middle part between anode and cathode, which corresponds to the described level in the above mentioned literatures.…”
Section: (15)mentioning
confidence: 99%
“…2) On the numerical modeling of DC plasma, many previous researches have been performed mainly on the free burning arc plasma in two-dimensional axisymmetric case. [3][4][5] In the thermofluid analyses described in the above literatures, the electric field is solved in the total region including an arc flow zone and both cathode and anode regions by giving heat flux condition between arc and electrodes without assuming the distributions of temperature and electric current on the electrode surfaces. The effects of arc current, inlet flow rate, electrode gap and cathode vertex angle on the thermofluid characteristics are clarified by two-dimensional computational simulation.…”
Section: Introductionmentioning
confidence: 99%
“…In the most of the previous numerical modelings, an arc flow and electrodes are treated separately and boundary conditions are partly given by using experimental data. [5][6][7][8] Furthermore, the influence of solid-liquid mushy zone 9) in molten anode on the molten pool structure has not been made clear yet so far.…”
Section: Introductionmentioning
confidence: 99%